ANALISIS PERBANDINGAN KINERJA REKSA DANA SYARIAH DENGAN REKSA DANA KONVENSIONAL JENIS SAHAM PADA PERIODE 2008 – 2012 - Amal Hamzah; Agustinus Yohanes (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: The objective of this study is to evaluate the performance of Islamic mutual funds compared to conventional mutual funds. Comparison of the two types of mutual funds is measured by return, risk, fund performance, and the ability of the Investment Manager of the two types of mutual funds. Research conducted on the types of shares mutual funds in the period 2008-2012. Fund performance measured by return and risk (portfolio beta and standard deviation), Sharpeindex, Treynor index, index of Jensen's Alpha, Modigliani and Modigliani (MM)model, and Treynor and Treynor (TT) model. The ability of the Investment Manager is evaluated in terms of security selection and market timing ability as measured by Henriksson-Merton and Treynor-Mazuymodel.The statistical method used to test the hypothesis is Independent T Test. The results showed in general there are nosignificant differences between Islamic mutual funds with conventional mutual fund.Keywords: performance, mutual fund, sharia, conventional